Electromyography as a Biofeedback Tool for Rehabilitating Swallowing Muscle Function - Steele, Catriona M.; Bennett, Janice W.; Chapman-Jay, Sarah; Polacco, Rebecca Cliffe; Molfenter, Sonja M.; Oshalla, Mohamed (IntechOpen, 2012)
None